Attitudes and reported practice of paediatricians and child psychiatrists regarding the assessment and treatment of ADHD in Ireland. (24th July 2017) - Honorio Neto, F.; Tatlow-Golden, M.; Mulligan, A.; Gavin, B.; McNicholas, F.
Abstract : Objectives: This mixed-method national survey has obtained original data on attention deficit hyperactivity disorder (ADHD) attitudes, assessment and treatment regimes reported by paediatricians and child psychiatrists; and has compared their clinics. It has examined the extent of involvement of Irish paediatricians in the management of ADHD. Methods: A questionnaire was designed, based on a review of literature and ADHD guidelines, and piloted by expert clinicians. Universal recruitment was conducted among Child and Adolescent Mental Health Services (CAMHS) consultants ( n =71) and community/general paediatric consultants ( n =72). Quantitative and qualitative data was collected and analysed. Results: There was an overall response rate of 43%. A dedicated ADHD clinic is offered in 79% of CAMHS services, but only in one paediatric service. Participants reported that the assessment of ADHD involves multidisciplinary work and this was only established in CAMHS clinics. Medication is initiated by 82% of child psychiatrists and only 22% of paediatricians. Conclusions: This first national study of ADHD attitudes and practices presents comprehensive data regarding the management of children with ADHD in CAMHS and paediatric settings in Ireland. Paediatricians reported a minor role in managing ADHD. Study limitations are related to subjective reporting rather than case note audit, and a moderate response rate for the paediatricians' participants.